Attempts to form the 10-nm-order pitch of self-assembled nanodots using PS-PDMS block copolymer. (21st April 2014) - Huda, Miftakhul; Liu, Jing; Mohamad, Zulfakri Bin; Yin, You; Hosaka, Sumio
Block copolymer (BCP) self-assembly exhibits its ability to form various nanostructures with a size down to 3 nm, which is particularly attractive for emerging technologies such as bit patterned media (BPM). Poly(styrene-b-dimethyl siloxane) (PS-PDMS) has been acknowledged as the most promising block copolymer for self-assembly fabrication due to its possibility to form nanopattern with a fine pitch, high etching selectivity, and its characteristic of robustness for pattern transfer. Here, we attempt to form PS-PDMS self-assembled nanodot array with a 10-nm-order pitch in order to satisfy the demand of low cost technique to form ultrahigh density nanodot array for BPM, which is regarded as the next-generation magnetic recording media, and for quantum devices such as the third-generation quantum dot photovoltaic cell and future battery cell. In this study, self-assembled nanodot array on a large area with pitches of 11 nm ( σ = 2.08 nm) and 10 nm ( σ = 1.61 nm) was formed using PS-PDMS with molecular weights of 5600–1300 g/mol (minority block volume fraction fPDMS = 19.8%) and 4700–1200 g/mol (fPDMS = 21.4%), respectively. In experiments, it was shown that some critical parameters, such as the thickness of PS-PDMS film, the treatment of the substrate surface, and annealing condition, played crucial roles in forming 10-nm-order size of self-assembled nanodot array using PS-PDMS. The relationships between pitches of PS-PDMS nanodot array and the product of the total number of segments and the Flory-Huggins segmental interaction parameter (χN) obtained by calculations and experiments will be discussed. Based on the position of PS-PDMS on mean-field phase diagram for BCP melts, the possibility to form nanodot array with a pitch of less than 10 nm is described. This study promises to open way toward the fabrication of more than 7.45 Tbit/in. 2 storage devices and the application of quantum devices.